A review of hotels’ survival strategies during COVID-19 pandemic in Malaysia / Fauziah Deraman ... [et al.] - Deraman, Fauziah; Ismail, Noralisa; Hamzah, Siti Nurhaliza; Tuan Zainudin, Tuan Zulaikha Atiqah (2021)
The study is about the strategies to help the hotel industries survive during the COVID-19 pandemic. Since this pandemic never happens before, the hotel industries are not ready to face such challenges in the business. Since the COVID-19 first outbreak, many businesses were affected and experienced a dramatic drop in the sales and revenue which no exception for hotel industry. For that reason, a study regarding the strategy or plan on how to make the hotel industries survive and avoid shutting down was conducted to help the business which had reached a dead end. Therefore, the objective of this study is to analyse the hotels’ strategies to survive during COVID-19 pandemic. In this study, the secondary data method was used to obtain data from recent studies by other researchers from academic journals, articles, and websites from the trusted sources. There are three strategies that was often applied by hotels in other countries which are cutting cost, becoming a quarantine hotel, and having pricing strategy. These strategies had shown a positive result and suitable to be applied by the hotels during COVID-19. The findings of this study can help the top management of the hotels to find the solutions on how to generate revenue and to sustain longer in the industry. Plus, hoteliers also can come out with a new polished strategy in the future and help them winning the battle against COVID-19.